A miner's lament. - Rom, Dongeto; Papag, Ron M.; Saturay, Ariel; Velasco, Jun; Valerio, Raquel E.; de Hitta, Helen (IBON Video Collection (AV031), 1997)
A stirring exposition on the effects of open-pit mining in Itogon not only to mine workers but also to the indigenous of Cordillera.